2006
DOI: 10.1538/expanim.55.35
|View full text |Cite
|
Sign up to set email alerts
|

The Region-Specific Functions of Two Ubiquitin C-Terminal Hydrolase Isozymes along the Epididymis

Abstract: We previously showed that gad mice, which are deficient for ubiquitin C-terminal hydrolase L1 (UCH-L1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…In gad mice, the levels of the antiapoptotic proteins Bcl-2/Bcl-xL were significantly elevated in the caput epididymidis regardless of efferent duct ligation. These results demonstrate that the two UCH isozymes, UCHL1 and UCHL3, have distinct expression levels along the epididymis and apparent reciprocal functions in response to apoptotic stress [20], as was shown with cryptorchid stress [19].…”
Section: Uch-l1 and Uch-l3 Have Region-specific Expression Along The supporting
confidence: 69%
“…In gad mice, the levels of the antiapoptotic proteins Bcl-2/Bcl-xL were significantly elevated in the caput epididymidis regardless of efferent duct ligation. These results demonstrate that the two UCH isozymes, UCHL1 and UCHL3, have distinct expression levels along the epididymis and apparent reciprocal functions in response to apoptotic stress [20], as was shown with cryptorchid stress [19].…”
Section: Uch-l1 and Uch-l3 Have Region-specific Expression Along The supporting
confidence: 69%
“…Therefore, it is conceivable that UCH-L1 and UCH-L3 have different functional roles in oocytes and embryos, as was shown in the testis/ epididymis. 9,11 Although our studies show that UCH-L3 is highly expressed in the cytoplasm of oocytes and embryos, we found no difference in the fertilization rate and litter size in Uchl3 knockout female mice compared with wild-type (C57BL/6J) female mice (data not shown). Thus, UCH-L3 may not impact these developmentally related processes; further research is necessary to elucidate the cytoplasmic function of this UCH.…”
Section: Discussionmentioning
confidence: 56%
“…[43][44][45] Our previous studies suggested that UCH-L1 and UCH-L3, despite their high sequence homology, 12 have distinct expression patterns and differential function in testis and epididymis. 9,11 Here we show that these two proteins have distinct distributions: UCH-L1 is exclusively expressed on the plasma membrane of oocytes and embryos, whereas UCH-L3 is diffusely expressed in the cytoplasm (Figures 1B and 2B). Therefore, it is conceivable that UCH-L1 and UCH-L3 have different functional roles in oocytes and embryos, as was shown in the testis/ epididymis.…”
Section: Discussionmentioning
confidence: 71%
“…We report here an additional modification that may significantly have an impact on its enzymatic and/or binding activities: UCH-L1 is farnesylated and associated with neuronal membranes, including the endoplasmic reticulum. This modification is not present in UCH-L3, which appears to serve different biochemical and biological roles than UCH-L1 (22)(23)(24)(25)(26)(27)(28)(29). The amount of membrane-associated UCH-L1 (UCH-L1 M ) is linked to intracellular ␣-synuclein levels and neurotoxicity.…”
mentioning
confidence: 99%